STUDY PHYTOCHEMICAL ETHANOL EXTRACT FRACTIONS AND LEAVES OF PIPER ADUNCUM "MATICO" - Arroyo A., J. (2011)
We worked with Piper aduncum L. "matico" Junin (Peru). The phytochemical analysis showed the presence of: saponins, tannins, quinones, flavonoids and alkaloids. For chromatographic analysis shows that there are more polar metabolites. The chemical markers and methanolic total ethanolic extract are flavonoids and alkaloids. The amount of total polyphenols was determined.